Higgs boson pair production at the LHC in the bbW+W- channel - Papaefstathiou, Andreas (2013)
We consider Higgs boson pair production at the LHC in the b ¯bW+W− channel, with subsequent decay of the W+W− pair into `νjj. Employing jet substructure and event reconstruction techniques, we show that strong evidence for this channel can be found at the 14 TeV LHC with 600 fb−1 of integrated luminosity, thus improving the current reach for the production of Higgs boson pairs. This measurement will allow to probe the trilinear Higgs boson coupling λ.